First Step in Developing an ICF Core Set for Adults with Cystic Fibrosis: A Systematic Review - Nisa Akyazı; Seda Nur Kemer; Naciye Vardar Yağlı; Melda Sağlam; Ebru Damadoğlu; Oğuz Karcıoğlu; Sevil Bilgin (Hacettepe University Faculty of Health Sciences Journal, 2026)
Objectives: This is the first of four preparatory studies in the process of developing an International Classification of Functioning, Disability, and Health (ICF) Core Set for adults with Cystic Fibrosis (CF). The aim was to identify to what extent outcome measures in studies of adults with CF reported in the scientific literature reflect the ICF.Materials and Methods: A systematic literature review was performed on PUBMED, Scopus, and Embase, including publications from 2014 to 2024. Meaningful concepts were identified from the included studies and linked to the ICF using standardized linking rules.Results: From the 1343 publications found, 802 articles were randomly selected for abstract screening, and 143 studies met the inclusion criteria. The outcome measures in the studies were linked with body functions by focusing on “b440 Respiration functions” (86.01%). It was observed that body structures were addressed by focusing on the categories of “s4301 Lungs” (11.89%) and “s410 structure of cardiovascular system” (5.59%). It was linked with activities and participation by focusing on the categories of “d450 walking” (13.28%), “d4551 climbing”. It was linked with environmental factors by focusing on “e5800 health services” (13.28%), and “Chapter 4-attitudes’ (13.28%). Limitations in activities and participation and environmental factors were less frequently linked. Conclusion: In this systematic review we performed on CF, the focus of scientific research was on limitations in body functions. Body structures, activities and participation limitations, and environmental factors were assessed less frequently. In the next step, we will include the perspectives and experiences of experts and patients.